Plagiat dan Pembajakan sebagai Pelanggaran Hukum Hak Cipta - Damian, Eddy (Indonesian Journal of International Law, 2006)
For the last two decades, Indonesia has been participating in several international conventions, in the field of intellectual property protection. Two of the intellectual property infringements are plagiarism and piracy of protected works. A person doing an act of offering or presenting as one’s own the work of another, wholly or partly, in a more or less altered form or context is called plagiarsm. Plagiarism is an infringement in the case of works protected by copyright law. Plagiarism is not the only infringement of copyright law, as piracy in the fields of copyright and neighboring rights, but also considered as unlawful and against the law of copyright.